Komposisi sebagai elemen pemberi maklumat dalam teks multimodal kad permainan Jepun / Khairul Bariah Abd Latif Azmi - Khairul Bariah , Abd Latif Azmi (2016)
This study is a multimodal analysis of Japanese game card 47 Todofuken Obenkyo Karuta which means “47 Prefectures Learning Game Card”. This game card introduces the 47 prefectures in Japan through the use of the famous animated icon, Doraemon. Generally, this game card is used in schools in Japan for the purpose of teaching and learning, particularly among children. In Ambang Asuhan Jepun, University of Malaya, this game card is one of the teaching aids used to assist students to improve their Japanese language proficiency and their knowledge about the prefectures in Japan. The objective of this study are to identify and to describe the visual and textual elements in the Japanese game card 47 Todofuken Obenkyo Karuta. This study also looks at how the elements of visual and textual are combined in the game card to convey information for the purpose of teaching and learning. The main visual element of Doraemon is discussed from the perspective of its representation in the context of each prefecture, while the textual elements are analyzed in terms of their sentence meaning, sentence pattern and lexical choices. This study is carried out based on the compositional analysis theory developed in the framework of Visual Social Semiotics by Kress and van Leeuwen (1996, 2006). The elements in the game card are analyzed based on the 3 criteria of Information Value, Salience and Framing. In addition, to support the findings of the data analysis, a questionnaire is also conducted on a number of students in Ambang Asuhan Jepun which aims to obtain their perspective on the effectiveness of the use of Japanese game card 47 Todofuken Obenkyo Karuta as a teaching aid. Findings reveal that the visual and textual elements in Japanese game card 47 Todofuken Obenkyo Karuta are combined in an effective composition for the purpose ofteaching and learning, thus enables this game card to function as a suitable and effective teaching aid in Ambang Asuhan Jepun, University of Malaya to assist students to improve their knowledge about the prefectures in Japan. In addition to filling the existing research gap and contributing to the literature in the field of semiotics particularly multimodality, the implementation of this study has also responded to the suggestions from researchers and scholars for teachers to move from monomodal view in literacy to current pedagogical method based on multimodality, in which the implementation or application of multimodal method in pedagogy has been proven beneficial and effective in various fields.